Low-cost renewable hydrogen production using solar photovoltaic panel - Sonwani S.; Prasad R. (My University, 2025)
The present work focuses on the use of two coaxial polyvinylchloride (PVC) pipes for the fabrication of an electrolyser. Fine perforations in the lower part of the inner pipe were made for easy movement of ions via electrolytic material between the electrodes. The two electrodes (anodes and cathodes) were kept in the outer and inner pipes respectively. A photovoltaic panel was directly connected to the electrolyser to measure the performance of the electrolyser system at normal room temperature and pressure with 27 wt% potassium hydroxide solution. Water displacement burette flow meter was used for measurement of flow rates of the produced hydrogen and oxygen. The ef-fects of various operating parameters on hydrogen production, variation in open circuit voltage and short circuit current produced by the photovoltaic cell with solar intensity in the daytime and their effect on H2 flow rate, and utilization of this hydrogen gas in the hydrogen gas stove need to be studied further. The work concludes with an innovative design to prepare a simple and cheap alkaline electrolyser to produce hydrogen gas using solar energy from the photovoltaic panel that can be used in remote areas for cooking purposes.